Nilai Humaniora Dalam Pemanfaatan Iptek - Naufal Al Ghafiqi; Muhammad Solikin; Jagat Ari Widiana Putri NK; Linggar Manik; Rahmatun Nikmah (JPT : Jurnal Pendidikan Tematik, 2026)
This paper discusses the increasingly rapid developments in science and technology (IPTEK), which have had a significant impact on various aspects of human life. However, this progress also presents new challenges when used without considering humanistic values. The integration of humanistic values ​​such as empathy, morality, responsibility, and care in the use of IPTEK is crucial for technology to be useful for humanity. Based on theoretical studies and previous research findings, technological development that ignores the humanistic can trigger moral decline, weaken cultural identity, create social inequality, and even pose a threat to human rights. Conversely, the use of technology that aligns with humanistic values ​​encourages ethical, sustainable development and maintains harmony in human life. Thus, the balance between IPTEK and the humanistic is an important foundation for the creation of a modern civilization that is both advanced and humanistic.